2020
DOI: 10.3233/nre-203079
|View full text |Cite
|
Sign up to set email alerts
|

The man who used to shrug – one man’s lived experience of TBI

Abstract: BACKGROUND: Stress is common to the experience of TBI. Stressors challenge physical and psychological coping abilities and undermine wellbeing. Brain injury constitutes a specific chronic stressor. An issue that hinders the usefulness of a stressbased approach to brain injury is a lack of semantic clarity attaching to the term stress. A more precise conceptualisation of stress that embraces experienced uncertainty is allostasis. OBJECTIVE: An emerging body of research, collectively identifiable as 'the social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Interpretative phenomenological analysis (IPA) is one method particularly well suited to further exploring these idiosyncrasies (see Wilde and Murray, 2010 ; Drinkwater et al, 2013 ), the lived experiences that were noted in the present research, because: One, IPA is committed, in an idiographic manner, to the in-depth analysis of the lived experience concerning the phenomena on which it is focused. Two, IPA is a method focused on how experiential phenomena are understood from a particular perspective ( Drinkwater et al, 2013 ; Walsh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interpretative phenomenological analysis (IPA) is one method particularly well suited to further exploring these idiosyncrasies (see Wilde and Murray, 2010 ; Drinkwater et al, 2013 ), the lived experiences that were noted in the present research, because: One, IPA is committed, in an idiographic manner, to the in-depth analysis of the lived experience concerning the phenomena on which it is focused. Two, IPA is a method focused on how experiential phenomena are understood from a particular perspective ( Drinkwater et al, 2013 ; Walsh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased risk of developing perceived stress post-TBI. Indeed, stress is a common experience of TBI ( Walsh et al, 2020 ). de Frias et al (2003) demonstrated that anxiety was robustly related to an increase in self-reported use of compensatory strategies.…”
Section: Introductionmentioning
confidence: 99%